COVID-19 Related Knowledge among Dental Patients- A Questionnaire Survey - Freshteh Osmani; Saideh Ebrahimianbaghan (Cumhuriyet University, 2022)
Introduction: The novel coronavirus disease (COVID-19) is a serious pandemic that caused viral respiratory illness. The aim of this study was to evaluate knowledge of patients attended dental clinic about COVID-19 pandemic at birjand. Methods: This study was conducted among 270 attending patients to the dental clinics as a cross-sectional survey. They were asked to complete a standardized questionnaire. The sampling method was as counting all the participants. The questionnaire consisted of demographic information and covid-19 knowledge. After collecting the data, they were analyzed by descriptive statistical methods and chi-square test using SPSS software. Results: The study was performed in February 2021. Results of this study showed 19.5%, 30.6% and 49.9% of respondents had poor, fair and satisfactory level of toward covid-19 respectively. Above 65% of the responders answered correctly to all questions. Men had poorer information (P = 0.014) statistical tests released that, knowledge had a significant association with educational level, age and monthly income amongst responders (P <0.05). Conclusions: It was concluded that, their knowledge towards SARS-CoV-2 is generally good. Further steps need to be taken to educate the patient's about its transmission in a dental clinic. Also, training programs about mechanism of potential spread of COVID are suggested for the improvement of knowledge.